Analisis Kualitas Informasi Sistem Tracking Dalam Menurunkan Keluhan Pelanggan Di Spx (Shopee Express) Mamuju - Yani, Indri; Al-Isra, Muhammad Fikri; Yeni, Hari (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
The rapid growth of e-commerce has compelled logistics companies to provide shipment information systems that are accurate, transparent, and timely in order to minimize customer complaints. One crucial aspect of digital logistics services is the quality of information generated by tracking systems. This study aims to analyze the effect of the information quality of the Shopee Express (SPX) tracking system on the reduction of customer complaints in Mamuju. The study employs a quantitative approach using a survey method involving 55 respondents who are users of Shopee Express services. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that the information quality of the tracking system has a positive and significant effect on reducing customer complaints. Descriptively, the accessibility dimension received the highest evaluation, indicating that the application is easy for customers to use. However, the timeliness dimension received the lowest score, particularly in relation to delays in updating shipment status. These findings suggest that although the system is easily accessible, delays in information updates remain a major trigger of customer dissatisfaction and complaints. Therefore, it can be concluded that improving information accuracy and providing real-time status updates are key factors in minimizing customer complaints and enhancing trust in Shopee Express services.